3-(m-Tolyloxy)phthalonitrile - Zhang, Xian-Fu (International Union of Crystallography, 2008)
In the molecule of the title compound, C(15)H(10)N(2)O, the dihedral angle between the two benzene rings is 65.49 (9)°.